Anatomical and ultrastructural studies on gelatinous fibers in the organs of non-woody xerophytic and hydrophytic species - Piva, Tayeme Cristina [UNESP]; Machado, Silvia Rodrigues [UNESP]; Scremin-Dias, Edna (Canadian Science Publishing, 2019)
Gelatinous fibers (G-layer) occur widely in various organs and plant tissues of both primary and secondary origin, but they are best known in tension wood. Here, we describe the occurrence, distribution patterns, and structural features of G-fibers in non-woody species of xerophytes and hydrophytes in Brazilian Cerrado (dry soil) and Chaco (wet or periodically waterlogged soils). G-fibers were present in all of the studied species, but were more abundant and more developed in xerophytes. They were associated with the phloem of leaves and primary stems and with the xylem of three xerophytic species that exhibited incipient secondary growth. The G-layer was non-lignified and characterized by greater thickness, lower density, and loose appearance in relation to the secondary layers. Under a transmission electron microscope, G-fibers displayed two secondary parietal layers (S1 and S2) in Prosopis rubriflora Hassle. (xerophyte), three secondary layers (S1, S2, and S3) in Eriosema campestre Benth. var. campestre (xerophyte), and a single secondary layer (S1) in Ludwigia leptocarpa Nutt. (hydrophyte). In P. rubriflora, mature G-fibers exhibited a loose-appearing electron-lucent region (transition zone) between G-and S-layers (secondary layers). In addition to mechanical support, this study suggests the involvement of G-fibers in water storage.
Keywords: Anatomy; Cerrado; Chaco; G-layer; Ultrastructure